Analisis Faktor Risiko Ergonomi terhadap Keluhan Gangguan Muskuloskeletal pada Pekerja UMKM Pengrajin Alas Kaki di Kecamatan Ciomas - Mayasari, Dita; Susilowati, Indri Hapsari Hapsari (National Journal of Occupational Health and Safety, 2022)
Work activity on footwear Micro, Small, and Medium Enterprises (MSMEs) such as sitting work position, bending down, neck bend, long duration of work and uncertain can cause pain that lead to musculoskeletal disorder complaint. This research aim to analyze individual risk factors, occupational risk factors, work environment risk factors, and work equipment risk factors against musculoskeletal disorder complaint on footwear MSMEs workers in Ciomas district. This research using cross sectional study design. The result of the research showed that 84,7% of respondent have a musculoskeletal disorder complaint. On some risk factors researched, there was a significant relationship between individual risk factors smoking behavior and musculoskeletal disorder complaint on shoulder also between occupational risk factors back risk exposure and musculoskeletal disorder complain on neck. On equipment risk factors measurement, show that are only a few workstations that comply with anthropometric standard, there are open’s table on 4th,5th, and 8th’s MSME, sewing machines, and finishing table’s at 8th MSME.